A reflection of integrated multi-disciplinary course in built environment - Abdullah, Fadzidah; Azmin, Aida Kesuma (s.n, 2012)
Architectural education has been accused to focus too much on aesthetic values that only prepares graduates to be designers, rather than proficient architects. To be proficient architects, graduates are also required to gain the skill of monitoring and working collaboratively with many parties; such as quantity surveyors, landscape architects, planners, and engineers. Thus, a special course named Integrated Multi-disciplinary Project is designed to familiarize architecture students with the real practice environment, where they have to work collaboratively with students from other disciplines in built environment. This paper aims to investigate the effectiveness of the course in instilling leadership and teamwork skills among architecture students. The specific objectives of the research are to examine if the multi-disciplinary course enhance students understanding of architects‟ and other related professions‟ roles in built environment; to evaluate if the course effectively develop students‟ leadership skills; to assess if the course instils teamwork skills among students; and to identify measure of improvement possible for the course based on the reflection done. This research uses combination of qualitative and quantitative methods to achieve its objectives. Literature review will be done to analyses the current scenarios of architectural education that leads to criticism, and investigate on subject of collaborative working environment among students. In addition, survey will be conducted to get generalization of ideas in the effectiveness of the Integrated Multi-disciplinary course in enhancing students‟ collaborative and leadership skills. This study would outline the fundamental issues causing lack of professional competency among architectural graduates, focusing specifically on how contemporary architectural education train students to have proficient collaborative skills. Development of new instructional design that includes multi-disciplinary concept for teaching and learning architecture might be recommended.